OP0306 Subcutaneous secukinumab inhibits radiographic progression in psoriatic arthritis: analysis by prior anti-tnf therapy and concomitant methotrexate use. (12th June 2018) - van der Heijde, D.; Mease, P.; Landewé, R.; Mpofu, S.; Rahman, P.; Tahir, H.; Singhal, A.; Boettcher, E.; Navarra, S.; Zhu, X.; Readie, A.; Pricop, L.; et al.
Abstract : Background: Psoriatic arthritis (PsA) is associated with joint inflammation, characterised by synovitis, presence of erosions, joint space narrowing (JSN) and new bone formation leading to structural damage, increased disability and reduced quality of life. Secukinumab (SEC) provided significant and rapid clinical efficacy, and inhibition of radiographic progression in PsA patients (pts) in the FUTURE 5 study. 1 Objectives: To assess the effect of subcutaneous (sc) SEC on radiographic progression by prior anti–TNF therapy or concomitant methotrexate (MTX) use in the FUTURE 5 study. Methods: Adults (n=996) with active PsA, stratified by prior anti–TNF therapy (naïve and inadequate response/intolerance [IR]) were randomised 2:2:2:3 to sc SEC 300 mg with loading dose (LD), 150 mg LD, 150 mg no LD, or placebo (PBO) at baseline (BL), Wks 1, 2, 3, 4, and every 4 wks thereafter. 1 At Wk 16, PBO non-responders were switched to SEC 300 or 150 mg. Concomitant MTX (≤25 mg/week) was allowed. Radiographic progression (mean change in van der Heijde-modified total Sharp score for PsA [vdH-mTSS] and its components: erosion and joint space narrowing [JSN] scores from BL to Wk 24) was based on hand/wrist/foot X-rays obtained at BL, Wks 16 (non-responders) assessed by two blinded readers (plus an adjudicator if required). Average scores were used. Statistical analyses used linear extrapolation at Wk 24 for all PBO non-responders and for all other pts with missing Wk 24 X-rays. Results: At BL, 30% pts were anti–TNF-IR and 50% were on concomitant MTX. Radiographic progression was significantly inhibited at Wk 24 in the overall population with SEC vs PBO; mean change from BL in vdH-mTSS was 0.08 (300mg; p<0.01), 0.17 (150mg; p<0.05), –0.09 (150mg no LD; P <0.01) vs 0.50 (PBO). Lower radiographic progression (vdH-mTSS, erosion and JSN scores) was observed with SEC vs PBO regardless of prior anti–TNF therapy or concomitant MTX use (table 1). Conclusions: Subcutaneous secukinumab 300 mg with loading dose, and 150 mg with and without loading dose, inhibited radiographic progression in patients with active PsA. Low rates of radiographic progression were observed regardless of previous anti-TNF therapy or concomitant MTX use. Reference: [[1] ] ] Mease PJ, et al. Arthritis Rheumatol 2017;69(suppl 10). Disclosure of Interest: D. van der Heijde Consultant for: AbbVie, Amgen, Astellas, AstraZeneca, BMS, Boehringer Ingelheim, Celgene, Daiichi, Eli-Lilly, Galapagos, Gilead, Glaxo-Smith-Kline, Janssen, Merck, Novartis, Pfizer, Regeneron, Roche, Sanofi, Takeda, UCB, Employee of: Director of Imaging Rheumatology, P. Mease Grant/research support from: AbbVie, Amgen, BMS, Celgene, Janssen, Lilly, Novartis, Pfizer, SUN, and UCB, Consultant for: AbbVie, Amgen, BMS, Celgene, Covagen, Crescendo, Janssen, LEO, Lilly, Merck, Novartis, Pfizer, SUN, and UCB; speakers' bureau for AbbVie, Amgen, BMS, Celgene, Genentech, Janssen, Lilly, Pfizer, and UCB, R. Landewé Grant/research support from: Abbott, Amgen, Centocor, Novartis, Pfizer, Roche, Schering-Plough, UCB, Wyeth, Employee of: Director of Rheumatology Consultancy BV, Speakers bureau: Abbott, Amgen, Bristol-Myers Squibb, Centocor, Merck, Pfizer, Roche, Schering-Plough, UCB, Wyeth, S. Mpofu Shareholder of: Novartis, Employee of: Novartis, P. Rahman Consultant for: Abbott, AbbVie, Amgen, BMS, Celgene, Janssen, Novartis, Pfizer and Roche, pharmaceutical companies dealing with biologic agents in Rheumatology, H. Tahir Grant/research support from: Novartis, Pfizer, Consultant for: Abbvie, Novartis, Pfizer, UCB, Eli-Lilly, Janssen, A. Singhal Grant/research support from: AbbVie, Gilead, Sanofi, Regeneron, Amgen, Roche, BMS, Janssen, Lilly, Novartis, Pfizer, UCB, Astra Zeneca, MedImmune, FujiFilm, Nichi-Iko, Mallinckrodt, Speakers bureau: AbbVie, E. Boettcher Consultant for: Amgen, Roche, Eli Lilly, Pfizer, MSD, Novartis, Speakers bureau: Amgen, Roche, Eli Lilly, Pfizer, MSD, Novartis, S. Navarra Consultant for: Pfizer, Novartis, Astra-Zeneca, Janssen, Astellas, Roche, Speakers bureau: Pfizer, Novartis, Astra-Zeneca, Janssen, Astellas, Roche, X. Zhu Employee of: Novartis, A. Readie Shareholder of: Novartis stock, Employee of: Novartis, L. Pricop Shareholder of: Novartis stock, Employee of: Novartis, K. Abrams Shareholder of: Novartis stock, Employee of: Novartis